Perceptions of employability among London's low-paid: `Self-determination' or ethnicity? - Richard Croucher; Sumeetra Ramakrishnan; Marian Rizov; Diana Benzinger (Economic and Industrial Democracy, 2015)
We investigate how ethnicity, gender and other characteristics affect low-paid workers' perceptions of their employability in London's labour market, examining self-efficacy, ethnic and dual labour market theories. We find that perceptions vary considerably, both between genders and ethnicities and in the extent to which they are `justified' by human capital attributes. Optimism varies between genders and ethnic groups but individuals' perceptions vary to an even greater extent within genders and ethnic groups. Hence, individual-level `self-determination' explanations of these perceptions appear to have greatest explanatory power in this specific context though ethnic theories also have utility.
Keywords: J15; J17; J24; J28; J71; J82; 330; Diversity; dual labour market; employability; human capital; labour economy